THE PROTECTION OF LEGITIMATE EXPECTATIONS CONTRA LEGEM - Gedmintaitė, Audronė (Teisė, 2015)
The article considers the concept of legitimate expectations. It is discussed whether unlawful legal acts can create legitimate expectations to the individual who has reasonably relied on these acts. The article sets out the arguments against the recognition of the protection of legitimate expectations contra legem. At the same token it is demonstrated why under exceptional circumstances legitimate expectations based upon unlawful acts shall be protected. The overview of the relevant case-law of national courts leads the author to conclude that the legitimacy of expectation and its protection is not determined by the legitimacy of its source. While deciding the cases concerning the adjustment of the principle of prtection of legitimate expectations with the principle of legality, national courts mostly apply a balancing approach. The balancing approach gives the advantage of allowing the court to evaluate not only the legality of the expectations in question but also other relevant circumstances. This comprehensive evaluation is necessary in order determine whether the public interest really does outweig the harm to the indivdual.